Microenvironment‑driven resistance to B‑Raf inhibition in a melanoma patient is accompanied by broad changes of gene methylation and expression in distal fibroblasts - Kodet, Ondřej; Dvořánková, Barbora; Bendlová, Běla; Sýkorová, Vlasta; Krajsová, Ivana; Štork, Jiří; Kučera, Jan; Szabo, Pavol; Strnad, Hynek; Kolář, Michal; Vlček, Čestmír; Smetana, Karel; et al. (International journal of molecular medicine, 2018)
The incidence of malignant melanoma is rapidly increasing and current medicine is offering only limited options for treatment of the advanced disease. For B‑Raf mutated melanomas, treatment with mutation‑specific drug inhibitors may be used. Unfortunately, tumors frequently acquire resistance to the treatment. Tumor microenvironment, namely cancer‑associated fibroblasts, largely influence this acquired resistance. In the present study, fibroblasts were isolated from a patient suffering from acrolentiginous melanoma (Breslow, 4.0 mm; Clark, IV; B‑Raf V600E mutated). The present study focused on the expression of structural and functional markers of fibroblast activation in melanoma‑associated fibroblasts (MAFs; isolated prior to therapy initiation) as well as in autologous control fibroblasts (ACFs) of the same patient isolated during B‑Raf inhibitor therapy, yet before clinical progression of the disease. Analysis of gene transcription was also performed, as well as DNA methylation status analysis at the genomic scale of both isolates. MAFs were positive for smooth muscle actin (SMA), which is a marker of myofibroblasts and the hallmark of cancer stoma. Surprisingly, ACF isolated from the distant uninvolved skin of the same patient also exhibited strong SMA expression. A similar phenotype was also observed in control dermal fibroblasts (CDFs; from different donors) exclusively following stimulation by transforming growth factor (TGF)‑β1. Immunohistochemistry confirmed that melanoma cells potently produce TGF‑β1. Significant differences were also identified in gene transcription and in DNA methylation status at the genomic scale. Upregulation of SMA was observed in ACF cells at the protein and transcriptional levels. The present results support recent experimental findings that tumor microenvironment is driving resistance to B‑Raf inhibition in patients with melanoma. Such an activated microenvironment may be viable for the growth of circulating melanoma cells.
Keywords: senioři; Tumor Microenvironment; fibroblasty asociované s nádorem; nádorové mikroprostředí; Skin Neoplasms; lidé; Melanoma; transkriptom; Cancer-Associated Fibroblasts; Point Mutation; Tumor Cells, Cultured; bodová mutace; Transcriptome; chemorezistence; ženské pohlaví; melanom; Humans; Drug Resistance, Neoplasm; metylace DNA; nádory kůže; Proto-Oncogene Proteins B-raf; DNA Methylation; protoonkogenní proteiny B-Raf; Melanoma, Cutaneous Malignant; Female; Aged; nádorové buňky kultivované; maligní melanom kůže